The influence of adaptive physical education on physical health and fitness of students with disabilities - Adyrkhaiev, Soslan; Adyrkhaieva, Liudmya (Social Welfare: Interdisciplinary Approach, 2017)
The article presents the results of the performed analysis of physical health and fitness of students with disabilities during their study at university if they use, in accordance with their medical conditions, the structural and functional technique of adaptive physical education proposed by the authors. The long-term experimental research with the proposed authors’ techniques has shown positive changes in the studied students’ physical health and fitness, which depend on the content and forms of their adaptive physical education. The main directions of improvement of physical health and fitness of students with disabilities during the classes of adaptive physical education are substantiated.The obtained results prove that the variety of medical conditions, accompanying disorders, lack of motivation for motor activity require a personal approach to a person with disabilities, selection of an individual path for his/her physical development. The results testify also to integration of students with disabilities into the student environment where they feel comfortable and more confident.
Keywords: students with disabilities; adaptive physical education; motor activity; medical conditions; physical exercises